Penggunaan Aplikasi Mobile Mindfulness GFR Bermanfaat untuk Mengelola Stres Mahasiswa di Akademi Keperawatan YKY Yogyakarta - Nunung Rachmawati (Health Information : Jurnal Penelitian, 2020)
The student is one of the academic stress-prone classes. Academic stress may be brought on by busy classes, overcrowded classes, laboratory examinations, and written examinations. Using technology can help students individually handle stress. The use of an android program named "Get Fresh and Relax" is expected to lower the stress levels of Yogyakarta students at the YKY Nursing School so that the student success index can be affected. This analysis used a quasi-experimental quantitative approach with the design of the control groups before and after research designs. 83 respondents with purposeful sampling were sampled in this analysis. It is known that the stress rate of the intervention group is significantly different from the control with a p-value < 0.05 based on research findings. This study concludes that it has a big impact on stressed students by using the GFR mobile consciousness framework.